The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1097/00004872-199917020-00013
|View full text |Cite
|
Sign up to set email alerts
|

Renal angiotensin II receptor regulation and reninangiotensin system inhibition in one-kidney, one clip hypertensive rats

Abstract: Angiotensin II receptors on preglomerular vessels and glomeruli are differentially regulated during the early phase of hypertension and after renin-angiotensin system blockade. Vascular angiotensin II receptors are upregulated in the early phase of hypertension whereas glomerular angiotensin II receptors are not However, after renin-angiotensin system blockade, glomerular but not vascular angiotensin II receptors were differentially regulated according to the type of blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
5
14
0
Order By: Relevance
“…In an additional set of experiments (n ϭ 6), we measured the plasma renin activity, which was markedly increased 4 weeks after renal artery clipping (3.9 Ϯ 1.3 v 1.8 Ϯ 0.33 ng/mL/h in sham-operated rats) and returned to basal values much latter (10 to 12 weeks post-clip). Similar results have been reported in the one-kidney, one-clip hypertensive model by Amiri et al 27 ) Angiotensin II is a powerful angiogenic substance in vivo and in vitro. 12 Munzenmaier and Greene 28 reported that subpressor angiotensin II infusion initiates angiogenesis in the rat cremaster muscle.…”
Section: Microvasculature and The Rassupporting
confidence: 89%
“…In an additional set of experiments (n ϭ 6), we measured the plasma renin activity, which was markedly increased 4 weeks after renal artery clipping (3.9 Ϯ 1.3 v 1.8 Ϯ 0.33 ng/mL/h in sham-operated rats) and returned to basal values much latter (10 to 12 weeks post-clip). Similar results have been reported in the one-kidney, one-clip hypertensive model by Amiri et al 27 ) Angiotensin II is a powerful angiogenic substance in vivo and in vitro. 12 Munzenmaier and Greene 28 reported that subpressor angiotensin II infusion initiates angiogenesis in the rat cremaster muscle.…”
Section: Microvasculature and The Rassupporting
confidence: 89%
“…Studies in two-kidney, oneclip Goldblatt hypertensive rats demonstrated that glomerular AT1 receptors were decreased by 2 weeks after clipping, but vascular receptors were not decreased until 16 weeks (Amiri and Garcia, 1997). However, glomerular AT1 receptor density was not increased in the onekidney-one-clip model, although vascular AT1 receptor density was increased (Amiri et al, 1999). In the Ang II-infused rat model of hypertension, total kidney AT1 receptor mRNA levels and protein levels were not suppressed but were maintained by 2 weeks of Ang II infusion sufficient to cause marked hypertension (HarrisonBernard et al, 1999).…”
Section: Angiotensin II Receptorsmentioning
confidence: 98%
“…The AT1R is responsible for the classical actions of Ang II such as vasoconstriction, aldosterone release from the adrenal zona glomerulosa, salt retention in the renal tubules, and stimulation of the sympathetic nervous system. AT2R plays an important role in the growth, differentiation, and regeneration of neuronal tissue [132,133].…”
Section: Ang II Receptorsmentioning
confidence: 99%